2006
DOI: 10.1007/s11010-005-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations that Enhance or Repress the Aggregation Potential of SOD1

Abstract: Mutations in SOD1 cause FALS by a gain of function likely related to protein misfolding and aggregation. SOD1 mutations encompass virtually every domain of the molecule, making it difficult to identify motifs important in SOD1 aggregation. Zinc binding to SOD1 is important for structural integrity, and is hypothesized to play a role in mutant SOD1 aggregation. To address this question, we mutated the unique zinc binding sites of SOD1 and examined whether these changes would influence SOD1 aggregation. We gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…These multimers are SDS-resistant complexes, andremain intact after being boiled in Laemelli's sample buffer (typically containing 0.1-2.0% SDS and 5% b-mercaptoethanol). Other studies have also identified high molecular weight structures in denaturing SDS-PAGE in tissues from G93A mutant transgenic mice [31,32]. The SOD1 SDS-resistant complexes seen in SDS-PAGE generally ranges in size from dimers up to small oligomers (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…These multimers are SDS-resistant complexes, andremain intact after being boiled in Laemelli's sample buffer (typically containing 0.1-2.0% SDS and 5% b-mercaptoethanol). Other studies have also identified high molecular weight structures in denaturing SDS-PAGE in tissues from G93A mutant transgenic mice [31,32]. The SOD1 SDS-resistant complexes seen in SDS-PAGE generally ranges in size from dimers up to small oligomers (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The D83 residue coordinates zinc binding to SOD1, and is required for the correct folding of human SOD1 (37). Thus, mutating the D83 residue is likely to interfere with the correct folding of SOD1 and potentially affect SOD1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that mutant SOD1 has decreased half-life compared with WT SOD1 (42), and potentially the inability of D83G SOD1 to coordinate zinc may contribute to its instability (37,43,44). …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of mutant SOD1 in tissues from G93A mice had identified high molecular weight structures in denaturing SDS-PAGE that were interpreted to represent SDS-resistant complexes (16,41,42). The SDS-resistant high molecular weight SOD1 seen in SDS-PAGE generally ranges in size from dimers to molecules of a mass no larger than relatively small oligomers (no more than 10 -20 subunits).…”
Section: Discussionmentioning
confidence: 99%